Formulasi Microneedle Acne Patch Ekstrak Daun Belimbing Wuluh (Averrhoa bilimbi L.) - Fitriana, Mia; Sarwo, Laura; Maharani, Ni Ayu (BORNEO JOURNAL OF PHARMASCIENTECH, 2024)
Belimbing wuluh leaves (Averrhoa bilimbi L.) contain flavonoids, saponins, and tannins that can be used as antibacterials in acne treatments. Acne treatment requires good delivery so that it can penetrate into the epidermis. A preparation that can deliver active substances directly into the epidermis is a microneedle patch (MN) preparation. This study aimed to formulate a microneedle acne patch of ethanol extract of A. bilimbi leaves. A. bilimbi leaves were extracted using maceration method. MN preparation base was optimized using different base combinations namely Na-CMC:PVA, HPMC: PVA and PVP:PVA until the ideal MN base was obtained. The MN preparations obtained were tested for physico-chemical properties which included macroscopic tests, weight uniformity, drying shrinkage, pH, folding power and moisture absorption. MN optimization results showed that the combination of PVP and PVA formed a flexible MN base and needle. Formulation was then continued by varying the concentration of extracts in the MN. The results of the physical and chemical properties test of the MN preparation formula showed flexible characteristics, homogeneous and no bubbles in MN, yellow to blackish green in color, weights ranging from 0,063-0,163 g, drying shrinkage of 3.349-4.513%, pH in the range of 5.61-7.15, folding power >300x, and moisture absorption of 6.472%-8.33%. The conclusion of the study showed that the MN preparation formulas of A. bilimbi extract, namely F1, F2, F3 and F4 meet the requirements of good physico-chemical MN preparations.